Training Needs Assessment and Employee Skills Acquisition: Systematic Review of Strategies, Outcomes, and Best Practices - Gasper Kissoka; Salma Khatibu (Malacca: Journal of Management and Business Development, 2026)
The implications of Industry 4.0 for workforce reskilling in Sub-Saharan Africa, highlighting both the potential and the challenges necessitate significant employee’s skills development. This highlights the importance of Training Needs Assessment (TNA) in aligning skills with labor market demands, which is essential for achieving Sustainable Development Goals (SDGs) related to education and decent work. This review aims to investigate TNA and its implication to employees’ skills acquisition in Sub Sahara Africa. Multiple databases, including PubMed, Scopus, African Journals Online (AJOL), Google Scholar, and the World Bank Open Knowledge Repository were used to search relevant studies. The screening process involved a two-stage approach, resulting in 23 studies for detailed analysis. Data synthesis utilized thematic analysis to categorize findings into major themes, with a mixed-methods approach integrating both qualitative and quantitative data. A quality assessment was conducted using the Critical Appraisal Skills Programme (CASP) checklist for qualitative studies and the Newcastle-Ottawa Scale (NOS) for quantitative studies, ensuring methodological rigor. The thematic analysis reveals that effective TNA strategies often involve mixed-methods approaches, systematic assessments, collaboration with stakeholders, and alignment with labor market needs. The reported outcomes of these strategies include improved performance and employability, although barriers such as resource limitations and resistance are notable. The review highlights the necessity for tailored TNA approaches that address the unique socio-economic contexts of Sub-Saharan Africa, contributing to the global discourse on workforce development and informing evidence-based policies.